PENINGKATAN KEMAMPUAN BAHASA INGGRIS BIDANG PARIWISATA UNTUK GURU SMK PUTIKECWARA BATU - Kun Mustain; Zubaidi; Eka Listianing Rahayu; Isnaini Nur Safitri; Pritantina Yuni Lestari (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2021)
This community service aims to accommodate the needs of tourism vocational school teachers in improving English language skills, especially English for hospitality and tourism industry through online English language training. The participants are tourism English teachers at SMK Putikecwara Batu. This activity is expected to improve the quality of learning at the SMK Putikecwara Batu through improving the English language skills of the teachers, which will then be implemented in the classroom and help students improve their English language skills in the tourism sector, especially hospitality and tourism industry. This activity is carried out in four stages, namely planning (to determine the number of participants who will be involved and the materials needed in the training), surveys to schools (to ensure that the plans made are in accordance with the needs), training implementation, and evaluation (giving questionnaires to the participants related to the implementation and training materials).